Development of Learning Modules Based on the Halaqah Approach through the ADDIE Model - Al-Qanit Qurba; Azwar Ananda; Jasrial; Zuwirna (Postgraduate, University of Mataram, 2023)
This research is motivated by facilitating Fiqh learning which is expected to help students and increase the variety of teaching materials for modules based on the Halaqah method so that they are more active and happy in learning Fiqh. This research includes research and development. This research uses the ADDIE development model with 5 stages, namely analysis, design, development, implementation, and evaluation. The instruments in this research used validity and practicality test questionnaires, and student learning outcomes to test the effectiveness of the Fiqh module being developed. The results of this research and development show that the validity test results based on media expert questionnaire validation obtained an average score of 95.55% with valid criteria. while the validation results from material experts obtained an average value of 86.95% with valid criteria. Linguist validation obtained an average score of 87.69% with valid criteria. The results of the practicality test based on the Fiqh teacher response questionnaire obtained an average score of 95.65%. The results of the practicality test based on the student response questionnaire from the experimental class obtained an average score of 89.83. Meanwhile, for module accuracy, an average score of 91.33% was obtained in the very practical category.